THE INFLUENCE OF LEADERSHIP AND MADRASAH PRINCIPAL MANAGEMENT ON TEACHERS’ WORK MOTIVATION - Sudarman, Sudarman; Baharuddin, Baharuddin; Rusmin B, Muhammad (Idaarah: Jurnal Manajemen Pendidikan, 2025)
This study is a quantitative research employing the ex-post facto method conducted at MTsN Gowa, South Sulawesi. The research aims to analyze the influence of leadership and madrasah principal management on teachers’ work motivation. The study population consists of 53 individuals, including teachers, the school principal, staff, and administrative personnel. This research employs a saturated sampling technique, where the entire population is included as the sample. Data were collected through questionnaires distributed to respondents and analyzed using simple and multiple linear regression with the assistance of SPSS. The findings reveal that leadership and madrasah principal management do not have a significant influence on teachers’ work motivation at MTsN Gowa. These results suggest that other factors beyond leadership and management play a more dominant role in determining teachers’ work motivation. Nevertheless, effective leadership and sound management remain essential in creating a conducive work environment. Therefore, this study recommends that efforts to enhance teachers’ work motivation should consider other relevant factors and encourages further research to identify additional variables that significantly contribute to teachers’ motivation.